Ultrastructure of fresh and post thawed sperm of pejerrey Odontesthes bonariensis (Atheriniformes) - Garriz, Angela (2013)
In the present study it was showed for the first time the ultrastructural morphology of O. bonariensis sperm using electron microscopy techniques. Different kinds of abnormalities were described in fresh and post thawed sperm caused by crogenic protocols. Pejerrey spermatozoon is uniflagellated and is differentiated into three parts: a small roundish head (~1.80µm in length and 1.67µm in width), a midpiece or transitional region (~1.11µm in length and 1.56µm in width), and a long tail or flagellum (~29.08µm). Samples of fresh and post thawed sperm showed evidence of morphological anomalies affecting various intracellular compartments. Spermatozoa with swollen, ruptured, or absent membranes in the head showing excess of cytoplasm, and with alteration of the spatial orientation of the mitochondria were observed. A swollen flagellum was observed containing cytoplasmic vesicles, distributed along the whole length or concentrated in a restricted part of the tail. It was also found a high level of abnormalities (60%) in frozen sperm when compared with normal sperm (18%) reflecting the damage provoked by cryopreservation procedures.